Pengaruh Komponen Intellectual Capital terhadap Profitabilitas Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Albar, Saskia; Sangkala, Masnawaty; Anwar, Azwar (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research aims to determine the influence of intellectual capital components on the profitability of manufacturing companies listed on the Indonesian stock exchange. The population in this study are all cement sub-sector manufacturing companies listed on the Indonesian stock exchange. The sampling technique used was purposive sampling technique. Data collection was carried out using descriptive statistical tests and multiple linear regression analysis. The results of the analysis show that there is a positive and significant influence between Value Added Capital Employed (VACA) on the profitability of manufacturing companies listed on the Indonesia stock exchange for the 2018-2022 period. There is a positive and significant influence between Value Added Human Capital (VAHU) on the profitability of manufacturing companies listed on the Indonesia stock exchange for the 2018-2022 period. There is no positive and significant influence between Structural Capital Value Added (STVA) on the profitability of manufacturing companies listed on the Indonesia stock exchange for the 2018-2022 period. There is a positive and significant influence between Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA) simultaneously on the profitability of manufacturing companies listed on the Indonesia stock exchange for the 2018-2022 period.